Valores energéticos e ajuste de equações de predição da energia metabolizável do milho para leitões - Esteves, Lucas Antonio Costa (2015)
The aims of this study were to determine energy values and fit prediction equations for metabolizable energy (ME) from the chemical composition of corn for piglets. Two digestibility trials were accomplished, the first one using corn from 2nd crop, in which 40 castrated piglets were used, averaging 8.75 ± 0,22 kg of initial weigh, allotted in a randomized block design with ten treatments, four replicates and one animal per experimental unit; the second experiment was carried out using corn from 1st crop, following the same procedures of the first experiment, with animals averaging 9.48 ± 0.06 kg of initial weight. In each experiment the treatments consisted of a basal diet and nine corn cultivars replacing 25% of basal diet. The experiment lasted 12 days, being seven days adjustment period followed by five days period of total collection of feces and urine. Ferric oxide (Fe203) was used as fecal marker to define the beginning and end of the collection period. Dry matter(DM), starch (ST), neutral detergent fiber (NDF), acid detergent fiber (ADF), crude protein (CP), ether extract (EE), ash, calcium (Ca) and phosphorus (P) of the 2nd crop corn ranged from 85.77 to 88.23%; 62.06 to 63.79%; 11.34 to 12.5%; 2.5 to 3.65%; 7.06 to 7.97%; 1.88 to 4.61%; 0.83 to 1.11%; 0.02 to 0.046%, 0.186 to 0.261% and 3743 to 3967 kcal/kg NM, respectively. For the 1st crop these values ranged from 87.23 to 89.22%; 62.49 to 64.93%; 10.19 to 12.78%; 3.36 to 4.29%; 7.55 to 8.55%; 2.94 to 4.22%; 0.99 to 1.22%; 0.02 to 0.026%, 0.206 to 0.311% and 3870 a 3980 kcal/kg NM, respectively. The ME values ranged from 3143 to 3652 kcal/kg NM, for the 2nd crop cultivars, while for the corn of the 1st crop these values ranged from 3281 to 3509 kcal/kg NM. The fitted equations to predict the ME presented a low R2. It is concluded that the better fit to predict the ME of corn for piglets is represented by ME= - 6306.15 + 400.652ADF + 117.286ST + 24924,7Ca + 2489.66P - 148.406CP (R2=0,44), for 1st corn crop; ME = -7560.08 + 2.66895GE - 120.688ADF (R2=0,48), for the 2nd corn crop; and for the joint crops was fitted the equation ME= 2848.95 + 68.5714NDF + 161.938EE - 5563.51Ca - 1454.15P (R2=0,41).